Access to mass media and teenage pregnancy among adolescents in Zambia: a national cross-sectional survey - David Mukunya; Daniel Mwamba; Quraish Sserwanja; Abigail Sitsope Sepenu (BMJ Open)
Objective Teenage pregnancies and childbirths are associated with negative health outcomes. Access to health information enables adolescents to make appropriate decisions. However, the relationship between access to health information through mass media and teenage pregnancy has not received much attention in existing literature. We therefore examined the association between access to mass media and teenage pregnancy in Zambia.Design Cross-sectional.Setting Zambia.Participants Weighted sample of 3000 adolescents aged 15–19 years.Outcome measure Teenage pregnancy that included adolescents who were currently pregnant or had had an abortion or had given birth in the last 5 years preceding the survey.Results Out of 3000 adolescents, 897 (29.9%, 95% CI: 28.1% to 31.3%) were pregnant or had ever been pregnant. Majority of the adolescents resided in rural areas (55.9%) and had secondary education (53.6%). Adolescents who had exposure to internet, newspapers or magazines, radio and television were 10.5%, 22.6%, 43.1% and 43.1%, respectively. Adolescents who had daily access to newspapers or magazines (adjusted OR (AOR): 0.33, 95% CI: 0.13 to 0.82) or using internet (AOR: 0.54, 95% CI: 0.30 to 0.95) were less likely to be pregnant or to have had a pregnancy compared with those with no access to newspapers and internet, respectively.Conclusion Our study suggests that internet use and reading of newspapers or magazines may trigger behavioural change as an effective approach to reducing teenage pregnancy. Behavioural change communicators can implement mass media campaigns using newspapers, magazines and the internet to publicise adolescent health messages that can encourage adolescents to adopt healthy behaviours and prevent teenage pregnancies.